The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.ygyno.2020.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy is not indicated in patients with vulvar squamous cell carcinoma and only one occult intracapsular groin node metastasis

Abstract: Omission of adjuvant radiotherapy in patients with one intracapsular groin metastasis results in 1% isolated groin recurrence • Neither size of the metastasis nor lymph node ratio had a significant impact on the risk of groin recurrence. • Adjuvant radiotherapy is not recommended in patients with a single occult intracapsular lymph node metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The 5-year, disease-specific survival was 79% and overall survival was approximately 62%. The conclusion was that in such cases adjuvant radiotherapy can be safely omitted avoiding unnecessary toxicity and morbidity [ 149 ].…”
Section: Treatmentmentioning
confidence: 99%
“…The 5-year, disease-specific survival was 79% and overall survival was approximately 62%. The conclusion was that in such cases adjuvant radiotherapy can be safely omitted avoiding unnecessary toxicity and morbidity [ 149 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Finally, we report the results of Van Der Velden et al’s [ 40 ] study on 96 patients with single clinically occult intracapsular lymph node metastasis treated with no adjuvant radiotherapy after surgical procedure. All patients underwent radical local excision of the primary tumor and either unilateral or bilateral IFL.…”
Section: Resultsmentioning
confidence: 99%
“…Only one patient showed an isolated groin recurrence (on the contralateral side). The authors found that neither the size of the metastasis in the lymph node (<5 vs. ≥5 mm) nor the lymph node ratio had any impact on the groin recurrence rate and/or survival in this group of patients [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…NCCN 4 2022 [17] Any nodes that are grossly enlarged or suspicious for metastases during the unilateral inguino-femoral lymphadenectomy should be evaluated by frozen section pathology intraoperatively in order to tailor the extent and laterality of the lymphadenectomy. DGGG 5 2015 [18] Systematic inguino-femoral lymphadenectomy (= surgical staging of the inguinal region) must always include removal of both the superficial (inguinal) and the deep (femoral) lymph nodes below the cribriform fascia (expert consensus).…”
Section: Guidelines Regarding the Treatment Of Bulky Lymph Nodes In T...mentioning
confidence: 99%
“…The standard treatment for patients with squamous cell cancer of the vulva and a depth of invasion > 1 mm consists of a radical local excision of the primary tumor and either lymph node evaluation by sentinel node dissection (SLN) or primary inguinal femoral lymph node dissection (IFL) [3]. Adjuvant radiotherapy is recommended in patients with metastases in the nodes, with the exception of patients with a single clinically occult intracapsular metastasis [4].…”
Section: Introductionmentioning
confidence: 99%